Implementasi Gen Sakti: Pijat Tui Na sebagai Strategi Komplementer Pencegahan Stunting pada Balita - Maylinda Zuwairiya Puspasari; Fahreza Ramadhan; Tiara Easya; Ahmad Zaki Haikal; Valerie Kezia Elim; Fransisca Andini; Levina Anjani; Arving Lailatul (Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting remains a chronic nutritional problem with long-term consequences for children’s growth and development, necessitating effective community-based interventions. This community service program aimed to enhance the knowledge and skills of mothers and health cadres in applying Tui Na massage as a non-pharmacological approach to support stunting prevention. The program was conducted in Brumbun Village, Madiun Regency, through educational sessions, hands-on practice, and six-day assistance for two children. Evaluation using pre- and post-tests among 14 participants showed a significant increase in mean scores from 46 to 79 (72%). Observations during assistance indicated weight gain and improvement in symptoms such as vomiting and constipation. These findings demonstrate that Tui Na massage is an effective and practical intervention that can be integrated into community-based health services, contributing to sustainable efforts in stunting prevention.